KEPRIBADIAN TOKOH UTAMA DALAM NOVEL SIRKUS POHON KARYA ANDREA HIRATA - Anggara, Wahyu Faria Adi; Wardiani, Ririen; Munifah, Siti (STKIP PGRI Ponorogo Press, 2022)
Literary works are the result of the author’s imaginative thoughts or creations that display human life. Literary works in all its forms are commonly colored by the attitudes, beliefs and backgrounds of the authors. This article aims to describe the personality of the main character in the novel Sirkus Pohon by Andrea Hirata. The personality that is the focus of the analysis is divided into two domains, namely personality in the realm of consciousness and personality in the realm of the unconscious. This research method is descriptive qualitative with a text study design (library research). To analyze, the researcher used the basis of personality theory that was promoted by Gustav Jung. The data collection procedure was carried out by reading, listening, and taking notes. The data obtained in the form of words, phrases, sentences obtained from the object of research. Based on the results of the study, the main character in the Circus Tree novel has an honest awareness, does not want to be deceived, falls in love, is angry, is firm in his stance, has sharp intuition, is friendly, easy to get along with. Meanwhile, the personality in the unconscious level of the main character are easily influenced, nervous, believes in shamans and believes high school graduates are better than elementary school graduates.